Network Analysis and Actors #CancelOmnibusLaw on Twitter Social Media Using Social Network Analysis (SNA) - Sabrina Rahma Utami; Rika Nurismah Safitri; Yohanes Ari Kuncoroyakti (JCommsci - Journal Of Media and Communication Science, 2021)
Omnibus Law is the merging of several different rules into one law. RUU Cipta Kerja is one part of the Omnibus Law that attracts attention because it is considered detrimental to society. This caused a lot of rejection and protests from the society. The protest was held directly in the form of demonstrations in various regions of Indonesia and also in Twitter through #BatalkanOmnibusLaw. The purpose of this research is to find out the analysis of communication networks and identify influential actors in #BatalkanOmnibusLaw on Twitter. This research uses Social Network Analysis (SNA) methods and Computer-mediated Communication theory. Data is collected through Twitter from August 1-October 31, 2020. The process of analyzing and retrieving data is using Netlytic.org and Gephi software. The results showed that there were 62 actors with 153 interactions. Proximity between actors is worth 3, meaning close proximity and easy interaction between actors. The interactions created between actors are very few, uneven ,and the interactions that occur only one way. The #BatalkanOmnibusLaw is centered on ten actors, the most dominant account is @fraksirakyatid. Based on degree centrality analysis, closeness centrality, betweenness centrality, and eigenvector centrality the most influential actors in #BatalkanOmnibusLaw network are @fraksirakyatid and @walhinasional. Keywords: #BatalkanOmnibusLaw, Twitter, Actor, Communication Network